2020
DOI: 10.1097/brs.0000000000003760
|View full text |Cite
|
Sign up to set email alerts
|

Does Duration of Pain at Baseline Influence Longer-term Clinical Outcomes of Low Back Pain Patients Managed on an Evidence-Based Pathway?

Abstract: and Martin, D (2021) Does duration of pain at baseline influence longer-term clinical outcomes of low back pain patients managed on an evidence-based pathway? Spine, 46 (3). pp. 191-197.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The latter has recently been shown to affect other LBP treatment modalities. 21 Furthermore, the iron sucrose labeling used might have affected the MSCs' performance, since in a previous in vitro study, 18 this labeling somewhat delayed the onset of glycosaminoglycan synthesis. However, for all reported disc cell injection studies, pain relief has been reported to be between 50% and 90%, so the present study is overall relatively well in line with those.…”
Section: Discussionmentioning
confidence: 99%
“…The latter has recently been shown to affect other LBP treatment modalities. 21 Furthermore, the iron sucrose labeling used might have affected the MSCs' performance, since in a previous in vitro study, 18 this labeling somewhat delayed the onset of glycosaminoglycan synthesis. However, for all reported disc cell injection studies, pain relief has been reported to be between 50% and 90%, so the present study is overall relatively well in line with those.…”
Section: Discussionmentioning
confidence: 99%
“…All studies were from six western, high-income countries (Table 1). Of the 11 studies and service evaluation report from the UK, five studies were local manifestations of the NHS England National Low Back and Radicular Pain Pathway (NELBPP) [19][20][21][22][23], with three from the same regional implementation site, the North East of England (NERP) [19][20][21]. Seven Canadian studies related to three separate pathways [24][25][26][27][28][29][30].…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…Four American studies included two from one centre regarding a telehealth-assisted pathway [31,32]. Four pathways were described as regional, namely the Integrated Spine Assessment and Education Clinics (ISAEC) [30], the Saskatchewan Spine Pathway (SSP) [27][28][29], the NERP [19][20][21] and that of Fleuren et al [33]. Eleven papers considered lumbar related conditions [19-21, 24-26, 30, 34-37], eight were specific to radicular leg pain [17,18,22,23,[27][28][29]33], and eight studies included more general spine conditions [31,32,[38][39][40][41][42][43], although half of these stated that most participants had lumbar complaints [38,40,41,43].…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…Therapeutic interventions for FJ pain include intra-articular steroid injections, extracorporeal shockwave therapy, surgical treatment, medial branch nerve blocks and medial branch nerve radiofrequency ablation (RFA) [ 5 , 6 ]. RFA is an injection procedure that is used to treat several conditions, including chronic spinal pain.…”
Section: Introductionmentioning
confidence: 99%